Zeolite-Modified Fischer-Tropsch Synthesis - Shah, Rashed (Department of Chemical Engineering, 2014)
The improvement of the gasoline selectivity and quality with the addition of HZSM-5 to the Fe-FT process is evident from literature. The catalytic performance of the combined Fe-FT/HZSM-5 system has been observed to decline with time-on-stream, attributed to the migration of alkali from the Fe-FT catalyst tothe HZSM-5 zeolite. The catalytic performance of the combined Fe-FT/HZSM-5system has, however, been observed to considerably decline with time-on-stream, aphenomenon which has been attributed to the migration of alkali from the Fe-FT catalyst to he HZSM-5 zeolite. The objective of this study is to characterize and confirm the reported performance of the Fe-FT and combined Fe-FT/HZSM-5 catalyst systems in a stirred from top internal recycle reactor under typical high temperature FT conditions.